Form of Judge's Consideration Against Dispensation Early Marriage - Ali, Abdul Rahman A.; Puluhulawa, Fenty U.; Tijow, Lusiana M. (Damhil Law Journal, 2021)
The study aims to analyze the judgment of judges in granting early marriage dispensation at the Gorontalo Religious Court. This research belongs to the type of normative legal research with a statutory approach and a case approach. The data analysis technique used in this research is using qualitative data analysis. The results of this study show that the considerations of judges are classified into two, namely legal considerations and considerations of community justice. The negative impact arising from marriage under the age of marriage dispensation is: Husband and wife who marry under the age of age are prone to divorce; In terms of reproductive health prone to death in children and mothers; There will be a to poor; There is child exploitation. Positive Impact on the establishment of early marriage dispensation is: Useful to continue the chain of offspring; Can maintain and maintain the genitals; It can make Muslims more responsible; The achievement of peace and tranquility between husband and wife; Marriage plays a role in helping to maintain people's lifestyle.